1996
DOI: 10.1093/ageing/25.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Haemostatic Factors in Young and Elderly Subjects

Abstract: Morbidity and mortality from cardiovascular disease are more common in colder seasons, especially in elderly people. Previous studies have shown higher fibrinogen levels in old people in the winter months. The present studies of haemostatic factors in relation to age and season have shown that fibrinogen, tissue plasminogen activator (tPA), protein S and protein C levels are higher in old (aged 75 years and over) than young (aged 25-30 years) subjects while antiplasmin levels are lower in old people. Antiplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 16 publications
1
27
1
Order By: Relevance
“…8 This is supported by other smaller studies. 7,16 As well as seasonal effects, variable reports exist of a diurnal pattern in fibrinogen 12,22,23 and D-dimer, 24 -26 whereas t-PA shows a morning peak with levels that tend to decline during the day; 12,24,27,28 vWF has been reported to show no diurnal variation in 1 small study. 28 Diurnal variation may be an important source of heterogeneity or bias, and standardization for sampling time may be important in populationbased studies, as well as in using these variables for additional coronary heart disease risk prediction in individuals.…”
Section: Clinical Perspective P 1003mentioning
confidence: 92%
See 3 more Smart Citations
“…8 This is supported by other smaller studies. 7,16 As well as seasonal effects, variable reports exist of a diurnal pattern in fibrinogen 12,22,23 and D-dimer, 24 -26 whereas t-PA shows a morning peak with levels that tend to decline during the day; 12,24,27,28 vWF has been reported to show no diurnal variation in 1 small study. 28 Diurnal variation may be an important source of heterogeneity or bias, and standardization for sampling time may be important in populationbased studies, as well as in using these variables for additional coronary heart disease risk prediction in individuals.…”
Section: Clinical Perspective P 1003mentioning
confidence: 92%
“…It is possible that the seasonal pattern is a phenomenon of aging because it is not observed in young or early middle-aged healthy adults. 16,17,19 Van der Bom et al showed that the seasonal amplitude for fibrinogen was 0.29 g/L in those aged 55 to 75 years but increased to 0.43 g/L in those aged 75 years and older. 8 The seasonal heterogeneity in D-dimer (Table 1) was also small, with only 4% seasonal variation.…”
Section: Seasonal Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14] However, some other studies did not confirm these findings. [15][16][17] The variation in inflammatory response is even greater in patients with established ACVD confirming the dynamic inflammatory status in these patients. 18 Seasonal variations in the incidence of cardiovascular events have also been reported by several investigators with a peak in winter months.…”
Section: Introductionmentioning
confidence: 73%